Urethral duct invasion in female urethral melanoma - Jennifer Urban; Cheryl B. Bayart; John A. Taylor; Upendra Hegde; Faripour Forouhar; Soheil S. Dadras (Elsevier, 2016)
Primary melanoma of the genitourinary tract represents ≤1% of all melanomas and is a highly aggressive malignancy, usually presenting at an advanced stage. Primary urethral melanomas are often amelanotic, leading to difficulties in early clinical diagnosis and biopsy delays. Herein, we present the clinical follow-up and histopathology of two female patients with microscopic invasion of the urethral ducts, not illustrated by previous reports. This finding, verified by appropriate immunohistochemical markers, can be a useful clue in diagnosing amelanotic melanoma of the genitourinary tract. The pathology reporting for urethral melanoma should include the depth of invasion, mitotic index, the status of resection margins, perineural invasion and lymphatic invasion since they will likely have a bearing on the tumor's biological behavior. Herein, we report two female patients with urethral melanoma exhibiting urethral duct invasion. Moreover, we discuss pertinent histopathological and immunohistochemical features, along with oncogene mutational typing that may aid in confirming the diagnosis and identifying molecular target(s).